La décadence à la fin du XIXe siècle espagnol: une esthétique de la provocation - Xavier Escudero (Nordlit: Tidsskrift i litteratur og kultur, 2012)
Talking about Decadence in fin-de-siècle Hispanic literature involves delving into the great movement of modernism, and notably one of its expressions, literary bohemianism. In what way(s) do these concepts both make use of and take part in an aesthetic of transgression, or a provocative pose? What does Spanish decadentism really mean, and what are its expressions?